2020
DOI: 10.1051/matecconf/202032104016
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of α-titanium alloys at elevated temperatures

Abstract: Hot-deep drawing is an innovative processing technology to produce complex shaped sheet metal components with constant wall thickness from high-strength lightweight materials. For some aerospace and automotive applications oxidation resistance at medium to high temperatures is an important aspect. In terms of this titanium α-alloys are often used due to their balanced relation of strength and oxidation resistance. In the presented study the stress-strain characteristics of several α-titanium alloys were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, the practical temperature limits for CP-Ti in structural applications range from less than 427 °C (800 °F) to approximately 538 °C or 595 °C (1000 °F or 1100 °F), contingent on the specific chemical composition of titanium-based alloys. Distinctive properties, including good conductivity, efficient thermal transfer and a favorable thermal expansion coefficient, have garnered attention for titanium’s application in diverse industries, such as electronics, automotive and aerospace [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the practical temperature limits for CP-Ti in structural applications range from less than 427 °C (800 °F) to approximately 538 °C or 595 °C (1000 °F or 1100 °F), contingent on the specific chemical composition of titanium-based alloys. Distinctive properties, including good conductivity, efficient thermal transfer and a favorable thermal expansion coefficient, have garnered attention for titanium’s application in diverse industries, such as electronics, automotive and aerospace [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has promising properties in terms of mechanical and fatigue strength as well as fracture resistance [5]. Nawaya et al [6] studied the tensile properties of α-titanium alloys (including Ti KS1.2ASN) at elevated temperatures and it was observed that the alloys reach the maximum formability in a certain temperature range (in the paper it was approx. 600-650 °C), where a further increase leads to a reduction of formability.…”
Section: Introductionmentioning
confidence: 99%